Peran Strategis Profesi Hukum Di Era Society 5.0: Antara Inovasi Dan Etika Profesional - Faradiba Muhamad; Raja Basyarin; Ninik Akhirah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of Era 5.0 has brought significant transformations to the legal profession, requiring professionals to adapt while consistently upholding essential professional principles. This paper examines how legal practitioners adjust to technological advancements, maintain ethical standards, and contribute positively to society in the midst of digital change. Through a qualitative analysis, this study highlights the core characteristics of legal professions in this era, such as the use of digital tools and effective data management. The findings emphasize the need for legal professionals to uphold integrity and ethical values while embracing technological progress. This study offers meaningful insights for navigating the evolving legal landscape in Era 5.0.